2000
DOI: 10.1164/ajrccm.161.6.9905060
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Airway Involvement in Obliterative Bronchiolitis after Lung Transplantation

Abstract: As defined by the International Society for Heart and Lung Transplantation, the diagnosis of posttransplant obliterative bronchiolitis (OB) is based on histopathologic features and/or spirometric staging criteria, using FEV(1) to determine the extent of disease. However, this last parameter reflects an advanced bronchiolar process. The present study investigated whether physiologic parameters reflecting smaller airways dysfunction on one hand, and neutrophils in bronchoalveolar lavage fluid (BALF) on the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 18 publications
8
65
0
1
Order By: Relevance
“…With BOS development, BAL neutrophilia (and eosinophilia) increase [99][100][101][102] above levels seen in stable patients [26,101,103,104]. However, whether this is a specific feature of BOS or whether it reflects concomitant airway infection is still debated.…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…With BOS development, BAL neutrophilia (and eosinophilia) increase [99][100][101][102] above levels seen in stable patients [26,101,103,104]. However, whether this is a specific feature of BOS or whether it reflects concomitant airway infection is still debated.…”
Section: Human Studiesmentioning
confidence: 99%
“…This concern recently led to formulation of a revised classification system for BOS [17], which includes a new "potential BOS" stage (BOS 0-p) defined as a decrease in forced mid-expiratory flow rates (FEF25-75%) and/or FEV1 (table 3). The rationale for including FEF25-75% comes from studies that showed that this variable deteriorates before FEV1 at the onset of BOS [100,125,126]. The new BOS 0-p stage is meant to alert the physician and to indicate the need for close functional monitoring and for in-depth assessment using surrogate markers for BOS (see below).…”
Section: Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12 However, we used this criterion because it is recommended to be one of the diagnostic criteria for BO 25 in the disease category derived from obliterative bronchiolitis after lung transplantation as BO syndrome (BOS). 31,32 The criteria of BOS are based on the idea that recognition of small air way obstruction is more sensitive than that of decline of FEV1/FVC. 31 Otherwise, reduction of FVC would mask obstructive change, thus we considered that these criteria are reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The criteria of BOS are based on the idea that recognition of small air way obstruction is more sensitive than that of decline of FEV1/FVC. 31 Otherwise, reduction of FVC would mask obstructive change, thus we considered that these criteria are reasonable. Four patients were actually diagnosed according to these criteria.…”
Section: Discussionmentioning
confidence: 99%